Understanding farmer perceptions of trees on farms to increase adoption of agroforestry in Uttar Pradesh - Singh, Himanshi; Kumar, Devendra; Verma, Sanjay Kumar; Doharey, R.K.; Singh, Abhinav (Indian Journal of Extension Education, 2025)
A structured survey was administered in 2024-25 in Ayodhya district across various landholding categories to understand the perception of farmers about agroforestry practices that hold a significant potential in improving rural livelihoods and environmental resilience. A sample of 180 farmers was drawn using multistage random sampling. Correlation analysis was used to determine relationships between socio-economic parameters and farmers’ perception of agroforestry practices. The results revealed that approximately 77% of the sampled population have been practicing agroforestry, with boundary plantations being the most preferred (45%) among all. Analysis of socio-demographic variables showed a significant correlation with farmers’ perceptions. Education, land ownership, training, and knowledge were positively associated with favourable perceptions, while age showed a negative correlation. Major barriers identified during the survey included a lack of technical knowledge, insufficient extension services, and market uncertainties. The results indicated that despite recognizing multiple benefits of agroforestry systems, farmers require better institutional support, access to quality planting materials, and market linkages to expand adoption. Targeted interventions focusing on training programs, extension services, and credit facilities could bridge the gap between positive perceptions and actual implementation of diverse agroforestry practices in the region.